Viability of Timor deer stag (Cervus timorensis) spermatozoa extended in tris egg yolk diluent with different sources of carbohydrate and storage at room temperature - Mesang-Nalley, W. Marlene; Handarini, R; Purwantara, B (Indonesian Animal Sciences Society, 2007)
The successful sperm preservation, influenced by the capability of its extender on the maintenance the sperm quality during storage. The carbohydrate such as glucose and fructose were the common sugar added on the mammalian sperm extender to support their live and motility. The sucrose was the main carbohydrate in Timor deer stag seminal plasma. The experiment was conducted to evaluate the effect of carbohydrates in Tris egg yolk (TEY) extender on the motility and viability of stag sperm, stored in room temperature (27-28 oC). The semen was collected using electro ejaculator from five Timor deer stags at hard antler stage, 3-5 years old, body weight of 64-102 kg with normal testes. The semen was than evaluated macro-and microscopically and divided into 3 aliquots. Each of them was diluted with TEY-glucose (TEYG), TEY-fructose (TEYF) and TEY-Sucrose (TEYS) with the concentration of spermatozoa 100 x 106 ml-1. The extended semen was than stored at room temperature. The sperm motility and viability were evaluated every 3 hours. Result of the experiment showed that the semen volume was 2.06 ± 0.63 ml, pH 7.03±0.13, yellow white until creamy in color and the consistency ranged from normal to thick. The mass movement between ++ to +++ and the sperm motility was 68.67 ± 7.4%. The average of sperm concentration was 842.35 ± 258.14x106 ml-1, the viable sperm was 78.11 ± 3.61%, the sperm abnormality was 7.31 ± 2.98%. The percentages of sperm motility on TEYG (18.00 ± 17.63%) and TEYS (21.83 ± 15.92%) were higher compare to TEYF (4,00 ± 0,00%) extender in 24 hours observation. The percentage of sperm viability showed the same pattern. The sperm viability in TEYG (28.17 ± 20.06) and TEYS (24.00 ± 22.59%) (P<0.05) were significantly higher compare to TEYF (4.00 ± 0.00%). It is concluded that the deer stag sperm can use the three sugars for their nutrition source. The diluted sperm still can be used for artificial insemination after 12 hour storage. Key Words: Liquid Semen, Deer, Room Temperature, Carbohydrate